The story of music - Goodall, Howard (London : Chatto & Windus, 2013)
Music is an intrinsic part of everyday life, and yet the history of its development from single notes to multi-layered orchestration can seem bewilderingly specialised and complex. In his dynamic tour through 40,000 years of music, from prehistoric instruments to modern-day pop, Howard Goodall does away with stuffy biographies, unhelpful labels and tired terminology. Instead he leads us through the story of music as it happened, idea by idea, so that each musical innovation - harmony, notation, sung theatre, the orchestra, dance music, recording, broadcasting - strikes us with its original force.
Machine generated contents note: The age of discovery, 40,000 BC-AD 1450 -- The age of penitence, 1450-1650 -- The age of invention, 1650-1750 -- 4.The age of elegance and sentiment, 1750-1850 -- The age of tragedy, 1850-1890 -- The age of rebellion, 1890-1918 -- The popular age I, 1918-1945 -- The popular age II, 1945-2012.
Includes bibliographical references and index.
Keywords: Music -- History and criticism